The resources and methods of the shamite historians who recorded the news of the imams of Ahl Al-Bayt (as) in the first half of the eighth century AH - Luma Ibrahim Aziz Al ziraijy; Dr. Mohammad Reza Shahidi Pak; Dr. Imdad Turan (Journal of College of Education, 2024)
This research entitled (resources and methods of the shamites who recorded the news of the imams of Ahl Al-Bayt (peace be upon them)in the first half of the eighth century Hijri ) deals with the material written by those shamite historians in their historical writings of brief news or detail about the infallible imams of Ahl Al-Bayt(peace be upon them) and the study period was limited to the first half of the eighth century Hijri, where some historians appeared in this era, including Abu al-Fada, deceased 732 ah, the author of the 742 ah-the author of the book of perfection in the names of men and the famous historian Shams al-Din al-dhahabi, who died 748 ah-the author of the book of the history of Islam and the biography of the media of the nobility, these three historians followed what they wrote in their mentioned books of news and historical novels that singled out the imams of Ahl Al-Bayt (peace be upon him) in political, military and intellectual aspects .  We have also followed the various sources that Shamian historians relied on to criticize the news of the imams of Ahl al-Bayt (peace be upon them), whether those sources are purely historical or literary or the sources of the Hadith of the prophet and others. Where we talked about how they rely on the source and whether it is from the nearby sources or contemporary sources of the sham historians, and these sources include the book of Ibn Asaker the deceased 571 ah, known as the history of the city of Damascus, which is one of the indispensable literature in recording the news of the Levant and the figures related to that country, as well as the book of the deaths of notables and the news of time of Ibn khalkan the deceased 681 ah, and some sham historians, such as Jamal al-Din al-Muzi, paid attention to the sources closest to the era of the imams of Ahl Al-Bayt (peace be upon them), such as the book of the writings of Ibn Saad the deceased 230 ah and the successor of Ibn Al-Khayyat 240 ah and the deceased Dar Qatani 385 Ah . As for the approaches of the shamite historians in recording the news of the imams of Ahl Al-Bayt(peace be upon them), they differed among the shamite historians, some of whom were detailed in their details, such as Al-dhahabi in his two books mentioned above, and some of them were brief for this information, such as Abu al-Fada in his short book on the news of humans, and some of them were between this and that, such as Jamal al-Din al-Muzi in his book the refinement of perfection in the names of men . One of their methods of mentioning the sources of their information is that sometimes they mention the author's name and the title of his book in full, sometimes they mention it briefly, and sometimes they mention the name of the book only without referring to the author .In doing so, they document the sources of their historical information about the imams of Ahl Al-Bayt(peace be upon them).
Keywords: The resources, the curricula, the Shamian historians, the Imams of the Ahlul Bayt (AS), the eighth century AH.